DIRECTIONS OF DIVERSIFICATION OF TOOLS OF ECONOMIC COOPERATION OF TERRITORIAL COMMUNITIES - PANASENKO, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The relevance of the issue of diversification of the tools of economic cooperation of territorial communities in Ukraine has been revealed. The purpose of the study is to determine the directions of diversification of the toolkit of economic cooperation of territorial communities.It has been established that the real state of affairs on the ground is evidence that domestic regional policy is still low effective, and it has been proven that one of the leading reasons for this is the low initiative and capacity of local self-government bodies, in particular the use of such a tool as inter-municipal cooperation. It is noted that the use of this tool allows you to combine, attract, replace capital and assets, opportunities and potential, to weaken your own weaknesses and positions due to cooperation. The concept of the life cycle development algorithm of inter-municipal cooperation of the territorial community is proposed and developed. A toolkit for expanding inter-municipal community cooperation in the field of local economic development has been developed.In addition, balanced, rational and full-fledged inter-municipal cooperation is able to significantly expand and diversify the toolkit for stimulating local economic development of communities - participants in cooperation. In particular, it is advisable to try to implement as wide a range of economic instruments as possible, in particular in the following areas: financial and investment, budgetary, credit, grant, socio-economic.The practical significance of the research results lies in the expansion of the set of tools that local self-government bodies can use to intensify inter-municipal community cooperation in the field of local economic development.The scientific novelty of the research results lies in deepening the means of public management of local economic development.
Keywords: territorial communities; inter-municipal cooperation; community cooperation; local economic development; innovative activity; innovative infrastructure; public administration